“The Meeting” — “The Apartment” — “Conversations”: Politics of space in an inclusive project - A. O. Dunaeva (Шаги, 2022)
The article discusses the political (J. Ranciere) potential of inclusive art in Russia on the basis of the example of a St. Petersburg project that at various times was called “The Meeting” (2014—2016) — “The Apartment” (2017—2019) — “Conversations” (2019 — present). To back up her arguments, the author enters into a dialogue with the authors of the collective volume Performance and the politics of space: Theater and topology (2013), especially with one of its editors, Benjamin Wihstutz. She also draws her attention on Michel Foucault's concept of heterotopy and Claire Bishop's theory of participatory art. The development of the project is observed throughout several periods, from the search for the space of utopia (Foucault) in the territory of repertory theater to the self-organized space “The Apartment”, independent from official institutions. After that the “diffusion” of the spatial presence of the group takes place. Finally, the company returns to the theatrical stage, ready for working with the politicization of differences. The methodological proposal of the article is to expand the boundaries of the performance or theatrical event and refuse to fix them. The author thinks of the entire space-time duration of the projects “Meeting”, “Apartment”, “Conversations” as a single procedural performance “Meeting — Apartment — Conversations” (2014 — present), which has a number of intermediate results in the form of performances, media events, concerts, lectures, rehearsals and, in some cases, other events occurring in between.